Examining the practice of Shariah governance in Islamic financial institutions in Sri Lanka - Hilmy, Hayathu Mohamed Ahamed (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2018)
Shariah governance is the salient feature of Islamic finance that validates the entire operation of Islamic Financial Institutions (IFIs) as compliant with Islamic law and differentiate them from conventional financial institutions. The scarcity has been found in the literature that elaborates Shariah governance practices of IFIs in Sri Lanka though the outfit of Islamic finance reached two decades of services in the country. Considering the shortage of literature, this study intends to examine the legal aspects and the actual practices of Shariah governance in Sri Lanka's IFIs. This study examines the law and regulations on Shariah governance as well as identifies the macro and micro level application of Shariah governance in Sri Lanka. The literature observation and document analysis were applied to explore the relevant domestic and international regulation on Shariah governance in the country. The practice of Shariah governance has been examined through interview and document analysis to find out the compliancy of IFIs with the regulations and international Shariah standards they follow by highlighting three main areas of Shariah governance that are the process structure, Shariah supervisory board and accountability. As a qualitative study, the data were gathered through the primary sources such as the information derived from the interview with experts, legislations, international Shariah standards, annual reports and other institutional documents from the IFIs; and supported by the secondary data available in the literatures such as articles in journals, books, newspaper reports, the IFIs websites and the like. The findings of this study indicate that there is no legislation in Sri Lanka that legally enforces on Shariah governance framework at macro level. But, each IFIs has setup Shariah governance institutionally at micro level. However, the findings further explore the gaps and shortcomings in the practice of Shariah governance at IFIs in the abovementioned three main areas of Shariah governance practices. Based on the findings extracted from the analysis, the recommendations were put forward to enhance the Shariah governance practices in Sri Lankan IFIs which is the significant contribution of this study. To ensure the relevancy of the recommendations, the experts' views and the country's political, judicial and ethnic behaviors were also taken into consideration while formulating the policy recommendation.